Seroprevalence of mumps, varicella and rubella antibodies in children 1-16 years of age in eastern Turkey - Guergoeze, Metin Kaya; Yilmaz, Erdal; Goedekmerdan, Ahmet; Akca, Zehra; Dogan, Yasar; Akarsu, Saadet; Ayguen, A. Denizmen (Turkish J Pediatrics, 2006)
In this study, seroprevalence of mumps, varicella and rubella was investigated in 803 unvaccinated children in eastern Turkey whose ages ranged between 1 and 16 years. Mumps IgG, varicella IgG and rubella IgG antibody levels in all children were studied by enzyme-linked immunosorbent assay (ELISA) method. Information regarding socioeconomic characteristics, number of siblings and disease history was gathered for each participant. No significant difference in seropositivity was detected between girls and boys. Seroprevalence of mumps increased with age, with a seropositivity rate of 29.9% in children aged 1-4 years and of 88.8% in those aged 13-16 years. Seroprevalence of varicella increased with age, with a seropositivity rate of 26.8% in children aged 1-4 years and of 90.3% in those aged 13-16 years. Seroprevalence of rubella also increased with age, with a seropositivity rate of 47.3% in the children aged 1-4 years and of 89.2% in those aged 13-16 years. There was a statistically significant increase in the rate of seropositivity with advancing age through the group of 13-16 years old (p<0.05). In conclusion, in order to avoid mumps, varicella and rubella diseases and their possible complications, children should be vaccinated against these three diseases before the age of two, since seroprevalence increases with age.
Keywords: seroprevalence; mumps; varicella; rubella